98.9k views
3 votes
Look at image, thus is a homework problem i need help with, thank you!

Look at image, thus is a homework problem i need help with, thank you!-example-1
User Visevo
by
5.2k points

1 Answer

1 vote

The given expression is:


\sin (-t)-\sin t

Recall the definition of an odd function:


f(-x)=-f(x)

Since the sine function is an odd function, it follows that:


\sin (-t)=-\sin t

Substitute this into the given expression:


\sin (-t)-\sin t=-\sin t-\sin t

Simplify the expression:


-2\sin t

Substitute sin t =a into the expression:


\begin{gathered} -2(a) \\ =-2a \end{gathered}

Hence, the expression in terms of a is -2a.

The answer is -2a.

User MockerTim
by
5.2k points